2015
DOI: 10.1021/jacs.5b07672
|View full text |Cite
|
Sign up to set email alerts
|

The Scope of Direct Alkylation of Gold Surface with Solutions of C1–C4 n-Alkylstannanes

Abstract: Treatment of cleaned gold surfaces with dilute tetrahydrofuran or chloroform solutions of tetraalkylstannanes (alkyl = methyl, ethyl, n-propyl, n-butyl) or di-n-butylmethylstannyl tosylate under ambient conditions causes a self-limited growth of disordered monolayers consisting of alkyls and tin oxide. Extensive use of deuterium labeling showed that the alkyls originate from the stannane and not from ambient impurities, and that trialkylstannyl groups are absent in the monolayers, contrary to previous proposal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 68 publications
6
28
0
Order By: Relevance
“…In our case, the presence of Sn (Figure 3d and Figure SI-4c in the Supporting Information;X PS signals of Sn 3d 5/2 at 487.3 eV and Sn 3d 3/2 at 496.2 eV)s uggested the formationo f coordination compounds with the oxygen atoms of the free carboxylic moieties by releasing the chlorine groups, which produced negligible XPS signals (Figure 3e and FigureSI-4 di n the SupportingI nformation). This promotes the formation of thicker layers (Figure 4) than those reported for neutral compounds, [22][23][24] and that reported for am onolayer of mercaptopropionic acid. [28] An estimation of the thickness of the organic layer was carried out by calculating the average layer thickness based on the attenuation of the XPS Au 4f 7/2 peak following surface modification.…”
Section: Surface Characterisation By Pm-irras Xps and Electrochemistrymentioning
confidence: 56%
“…In our case, the presence of Sn (Figure 3d and Figure SI-4c in the Supporting Information;X PS signals of Sn 3d 5/2 at 487.3 eV and Sn 3d 3/2 at 496.2 eV)s uggested the formationo f coordination compounds with the oxygen atoms of the free carboxylic moieties by releasing the chlorine groups, which produced negligible XPS signals (Figure 3e and FigureSI-4 di n the SupportingI nformation). This promotes the formation of thicker layers (Figure 4) than those reported for neutral compounds, [22][23][24] and that reported for am onolayer of mercaptopropionic acid. [28] An estimation of the thickness of the organic layer was carried out by calculating the average layer thickness based on the attenuation of the XPS Au 4f 7/2 peak following surface modification.…”
Section: Surface Characterisation By Pm-irras Xps and Electrochemistrymentioning
confidence: 56%
“…We list below three general methods for in situ generation of AuC covalent contacts. The first method adopts the reactivity of CSnR 3 bonds based on transmetalation to generate AuC bonds on gold surfaces . However, this approach uses and produces toxic and volatile trimethyltin species, which limits its wide application.…”
Section: Interface Modification Methodsmentioning
confidence: 99%
“…More recent experiments with deuterated alkylstannanes showed that under the ambient conditions used this cannot be entirely correct. Although tin is co-deposited with the alkyls, it does not appear as a trialkylstannyl group, whose deuterated form would be detectable in IR spectra, but as a tin oxide, detected by XPS . In the one case in which the alkylation reaction order with respect to stannane concentration in bulk solution was determined, it was found to be 0.5.…”
mentioning
confidence: 95%
“…This treatment is known to coat a flat surface of gold, mostly Au(111), with an alkyl-containing monolayer . It is significant for at least two reasons: (i) the resulting layers are distinct from those commonly produced by treatment with alkanethiols in their permeability and thermal and chemical stability, and (ii) direct carbon-to-gold attachment has much higher electrical conductivity than attachment through a sulfur atom. , While methyl groups are not transferred from a tin atom to the Au surface and ethyl groups are transferred only very slowly, propyl and longer alkyl groups are transferred efficiently . Similar solution alkylation processes do not proceed under ambient conditions with alkylsilanes, but they do take place with the organomercurials RHgX. , …”
mentioning
confidence: 99%